Muslim Development at Risk: The Crisis of Human Resources (American Journal of Islam and Society, 1992)
Regardless of the definitions chosen, the conceptual frameworksadopted, or the analytical schemes utilized, many social analysts wouldagree that, even after decades of struggle for national development andmodernization, the state of underdevelopment in Muslim countries has notchanged significantly.' on most of the standad measures conventionallyused to make international comparisons as regards national development,Muslim countries occupy a disproportionate share of the bottom positions.While they languish there, the rest of the world thrusts forwad2 Despitethe oil wealth of the Muslim world, most Muslim countties remain on theperiphery of the emerging global economy and 8tp: becoming incteasinglymarginalized as newly industrialized Third World countries enter thecompetitive international marketplace. The Muslims' failure to transformtheir societies and become productive is due to their lack of knowledge,skills, and capabilities in most areas of intellectual endeavor, especiallyin the scientific and technical fields. More specifically, their inability touse the tools, techniques, and procedures of modem science for developmentalchanges is the result of deficiencies in their human resources.This paper examines the present status of human resoutces in theMuslim world and Assesses their prospects for the future direction of developmentand modernization. Its analysis is confined to the relationship ...